2018
DOI: 10.1038/s41419-018-1010-2
|View full text |Cite
|
Sign up to set email alerts
|

CCL19 suppresses angiogenesis through promoting miR-206 and inhibiting Met/ERK/Elk-1/HIF-1α/VEGF-A pathway in colorectal cancer

Abstract: The mechanisms underlying the role of chemokines in tumor angiogenesis is still not fully understood. In this study, we detected the influence of CCL19 on colorectal cancer (CRC) angiogenesis. The expression of CCL19 and CD31 in CRC tissues were detected by immunohistochemistry. Human CRC cell lines SW1116 and SW620 stably transfected with CCL19 lentivirus and CCL19 shRNA, and HUVEC stably transfected with CCR7 shRNA were used in our study. Our study showed that CCL19 was significantly low-expressed in CRC tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 50 publications
(54 reference statements)
4
107
0
Order By: Relevance
“…Our results revealed that cell lines transfected with miR-206 mimics experienced a significant down regulation of VEGF. Similar behavior has been reported previously in renal carcinoma [32], colorectal [33] and lung cancers [34]. These key findings indicate that miR-206 can suppress VEGF-mediated invasion and angiogenesis in TNBC.…”
Section: Discussionsupporting
confidence: 89%
“…Our results revealed that cell lines transfected with miR-206 mimics experienced a significant down regulation of VEGF. Similar behavior has been reported previously in renal carcinoma [32], colorectal [33] and lung cancers [34]. These key findings indicate that miR-206 can suppress VEGF-mediated invasion and angiogenesis in TNBC.…”
Section: Discussionsupporting
confidence: 89%
“…19,31 Inhibition of MET gene expression by miR-206 has been suggested to limit the development of various types of cancers. 9,11,[31][32][33][34][35] We found that miR-206 mimic transfection signicantly reduced c-Met protein level in patient-derived HCC cells, and restoring c-Met protein level by transient overexpression could partially restore the malignancy of HCC cells that were reduced by miR-206 mimic transfection in vitro, suggesting that inhibiting c-Met protein expression is implicated in the HCC-suppressive role of miR-206. We observed no signicant inuence on EGFR or IGF1R protein level in HCC cells by miR-206 mimic transfection (data not shown), although several previous reports have described the inhibition of EGFR gene expression by miR-206 via mRNA targeting in lung squamous cell carcinoma, 36 head and neck squamous cell carcinoma 37 and ovarian carcinoma cells.…”
Section: Discussionmentioning
confidence: 72%
“…7,8 MiR-206 is a cancer-suppressive microRNA in colorectal cancer, non-small-cell lung cancer, ovarian cancer and neck squamous cell carcinoma by suppressing the activation of PI3K-Akt and MAPK signaling pathways. [9][10][11][12][13] MiR-206 has also been described as a tumor-suppressive microRNA in HCC: miR-206 was found downregulated in HCC in association with advance in tumor stage and patients' worsened outcome, 14 and the antiproliferative/pro-apoptotic effects of overexpressing miR-206 in HCC cells in vitro were also reported. [14][15][16] However, molecular mechanisms underlying the HCC-suppressive role of miR-206 remain largely underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the expression of miR-206 was inhibited, the impaired migration ability of MSCs was partially alleviated (P < 0:001 compared to the H 2 O 2 group), whereas supplementation of levamisole significantly blocked such positive effects (Figures 6(a) and 6(b)). Further, to explore the paracrine function of rat MSCs, we cocultured HUVEC cells with the supernatants of MSCs in different groups for 24 hours and then performed tube formation assay as described previously [22]. As shown in Figures 6(c)-6(e), compared to the NC group, both the meshes numbers and tube lengths in the H 2 O 2 group showed a dramatic decrease (P < 0:01).…”
Section: Alpl Was a Target Gene Of Mir-206 As Depicted Inmentioning
confidence: 94%
“…Moreover, the HUVEC angiogenesis in the miR-206 inhibitor group was even superior to that in the NC group. Similarly, an in vitro study observed that CCL19 high-expressed SW1116 supernatant was able to inhibit the angiogenesis of HUVEC through promoting miR-206, whereas CCL19 low-expressed SW620 supernatant can promote HUVEC angiogenesis [22]. Besides, Wang et al have reported that amphiregulin enhanced VEGF-A production in human chondrosarcoma cells and promoted angiogenesis by inhibiting miR-206 via the FAK/c-Src/PKCd pathway [39].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 97%